MODULATING EFFECT OF THE −158 GΓ (C→T) XMN-1 POLYMORPHISM IN INDIAN SICKLE CELL PATIENTS - Sanjay Pandey; Sweta Pandey; Rahasya Mani Mishra; Renu Saxena (Mediterranean Journal of Hematology and Infectious Diseases)
Xmn-1 polymorphism is a known factor, which increases fetal haemoglobin production. Among the inherited disorders of blood, thalassaemia and SCD constitutes a major bulk of genetic diseases in India. Our aim was to verify the role of the Xmn I polymorphism as a modulating factor in sickle cell patients and frequency of the polymorphism in Indian sickle cell patients. Subjects were 60 sickles homozygous and 75 sickle beta thalassemia patients. 5 ml blood samples collected from patients. Screening of sickle patients done by HPLC. An automated cell analyzer SYSMEX (K-4500 Model) used to analyze the CBC of patients.Xmn1 polymorphism analysis done by PCR-RFLP and Statistical analysis was performed on GraphPad static’s software. t test applied to compare the means amongst group. Among the sickle homozygous 27 were heterozygous (+/-) and 19 were homozygous (+/+) while 30 were heterozygous and 24 were homozygous in sickle β-thalassemia patients. Extremely significant differences (p-value <0.001) of hematological parameters seen among patient with xmn-1 carrier and without the xmn-1 carrier. In our cases the clinical symptom less frequent and higher HbF level with Xmn-1 carriers. Presence of Xmn-1 polymorphism in sickle patients with higher HbF that improve phenotypic presentation in the sickle cell patients. We conclude that the phenotype of Indian sickle cell patients influenced by Xmn-1 polymorphism.